2019
DOI: 10.1590/s1677-5538.ibju.2018.0308
|View full text |Cite
|
Sign up to set email alerts
|

Robot assisted radical prostatectomy in kidney transplant recipients: surgical, oncological and functional outcomes of two different robotic approaches

Abstract: Background: To date, few series on robot-assisted radical prostatectomy (RARP) in kidney transplant recipients (KTRs) have been published. Purpose: To report the experience of two referral centers adopting two different RARP approaches in KTRs. Surgical, oncological and functional results were primary outcomes evaluated in the study. Material and methods: We retrospectively analyzed data from 9 KTRs who underwent transperitoneal RARP or Retzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
(73 reference statements)
1
19
1
Order By: Relevance
“…RS-RARP although more demanding than the conventional RARP with a longer learning curve is now considered a safe and feasible approach [14]. Mistretta et al in their series of 9 patients compared outcomes of standard RARP (4 patients) with RS-RARP (5 patients) and concluded that both approaches are safe and feasible in patients with renal transplants with equivalent functional outcomes and oncological outcomes [15]. Our study had comparable results with good oncological outcomes and excellent functional recovery.…”
Section: Discussionsupporting
confidence: 60%
“…RS-RARP although more demanding than the conventional RARP with a longer learning curve is now considered a safe and feasible approach [14]. Mistretta et al in their series of 9 patients compared outcomes of standard RARP (4 patients) with RS-RARP (5 patients) and concluded that both approaches are safe and feasible in patients with renal transplants with equivalent functional outcomes and oncological outcomes [15]. Our study had comparable results with good oncological outcomes and excellent functional recovery.…”
Section: Discussionsupporting
confidence: 60%
“…The initial electronic search identified a total of 6739 papers. Of these, 4780 publications were identified for detailed review, and ultimately only eight studies were found to meet the inclusion criteria and included in the analysis . Characteristics of the included studies are reported in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A high risk of bias (missing data, measurement of outcomes and selection of the reported results) was recorded for one retrospective study according to the ROBINS‐I tool, whilst a moderate risk of bias was recorded for the other retrospective studies . The three RCTs were mostly found to have a high risk of bias (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier systematic review, Checcucci et al [8]. It included only two RCTS [24,25], and five non‐RCTS [6,13,35–37]. Rather than analysing both bodies of evidence separately, the authors opted to pool across all studies, which is not recommended.…”
Section: Discussionmentioning
confidence: 99%